Regions of interest (ROI) for future exploration missions to the lunar South Pole. (January 2020) - Flahaut, J.; Carpenter, J.; Williams, J.-P.; Anand, M.; Crawford, I.A.; van Westrenen, W.; Füri, E.; Xiao, L.; Zhao, S.
Abstract: The last decades have been marked by increasing evidence for the presence of near-surface volatiles at the lunar poles. Enhancement in hydrogen near both poles, UV and VNIR albedo anomalies, high CPR in remotely sensed radar data have all been tentatively interpreted as evidence for surface and/or subsurface water ice. Lunar water ice and other potential cold-trapped volatiles are targets of interest both as scientific repositories for understanding the evolution of the Solar System and for exploration purposes. Determining the exact nature, extent and origin of the volatile species at or near the surface in the lunar polar regions however requires in situ measurements via lander or rover missions. A number of upcoming missions will address these issues by obtaining in situ data or by returning samples from the lunar surface or shallow subsurface. These all rely on the selection of optimal landing sites. The present paper discusses potential regions of interest (ROI) for combined volatile and geologic investigations in the vicinity of the lunar South Pole. We identified eleven regions of interest (including a broad area of interest (>200 km × 200 km) at the South Pole, together with smaller regions located near Cabeus, Amundsen, Ibn Bajja, Wiechert J and Idel'son craters), with enhanced near-surface hydrogen concentration (H > 100 ppm by weight) and where water ice is expected to be stable at the surface, considering the present-day surface thermal regime. Identifying more specific landing sites for individual missions is critically dependent on the mission's goals and capabilities. We present detailed case studies of landing site analyses based on the mission scenario and requirements of the upcoming Luna-25 and Luna-27 landers and Lunar Prospecting Rover case study. Suitable sites with promising science outcomes were found for both lander and rover scenarios. However, the rough topography and limited illumination conditions near the South Pole reduce the number of possible landing sites, especially for solar-powered missions. It is therefore expected that limited Sun and Earth visibility at latitudes >80° will impose very stringent constraints on the design and duration of future polar missions. Highlights: There is increasing evidence and interest for cold-trapped volatiles around the South Pole. Several areas of interest are suitable for future investigations of both lunar volatiles and regional geology. Case studies illustrate that precise landing site selection is highly mission dependent. Illumination and Earth visibility remain limited around the South Pole and will strongly impact future mission scenarios.